Cover Image. Issue 4 (9th January 2023) - Wang, Zhicheng; Li, Anqiao; Zheng, Yixiao; Xie, Anhuan; Li, Zhibin; Wu, Jun; Zhu, Qiuguo; Xu, Haochen; Yu, Zhangguo; Chen, Xuechao; Dong, Chencheng; Chen, Huanzhong; et al.
Abstract : The cover image is based on the Research Article Efficient learning of robust quadruped bounding using pretrained neural networks by Zhicheng Wang et al., https://doi.org/10.1049/csy2.12062 . and Original Article Disturbance rejection for biped robots during walking and running using control moment gyroscopes by Haochen Xu et al., https://doi.org/10.1049/csy2.12070 .